Biliary tract abnormalities in patients with autosomal dominant polycystic kidney disease: Incidence and magnetic resonance cholangiopancreatography findings - Murat GÜRSOY,; Beril AKMAN,; Muhteşem AĞILDERE,; Aslı DOĞRUK,; Cüneyt AYTEKİN,; Nurhan ÖZDEMİR,; Sedat BOYACIOĞLU, (Turkish Journal of Gastroenterology, 2019)
-